Birth prevalence of Prader-Willi syndrome in Australia. Issue 3 (1st March 2003) - Smith, A; Egan, J; Ridley, G; Haan, E; Montgomery, P; Williams, K; Elliott, E
Abstract : This is the first population based study to estimate the birth prevalence of DNA proven Prader-Willi syndrome. Thirty infants were reported to the Australian Paediatric Surveillance Unit between 1998 and 2000, a prevalence of 4 per 100 000 live births or ∼1/25 000 live births per annum.